Application of potential field method and optimal path planning to mobile robot control - Chia-Chia Kao; Chih-Min Lin; Jih-Gau Juang (2015 IEEE International Conference on Automation Science and Engineering (CASE), 2015)
The objective of this study is to apply differential global positioning system (DGPS) and an improved artificial potential field (APF) method to a wheeled mobile robot (WMR) for path planning under unknown environment. A laser sensor is utilized to detect obstacles and surroundings. With the distance information given by the laser sensor, the repulsive force is used for collision-free of the WMR. By the iterative closest point (ICP) algorithm, the rotation and translation information can be calculated and utilized to aid the position and attitude determination. Fuzzy theory is applied to change the attractive factor to improve the zigzag trajectory. To deal with the local minimum problem, we add the path finding method A* algorithm to find the shortest unblocked path to destination. With the integration of fuzzy rule, positioning and path finding algorithms, the APF can be created. The experiments confirm that the proposed control scheme works properly.